Hybrid Photovoltaic and Wind Power System with Battery Management System Using Fuzzy Logic Controller - M. Venkateshkumar; R. Raghavan (Institute of Advanced Engineering and Science, 2016)
In recent year, the development of hybrid renewable energy sources has the important role of power generation. This paper focused on design of hybrid PV / Wind power system and its battery management system. The fuzzy logic control based battery management system has been designed for effective power utilization. The proposed control to operate the battery charging and discharging mode during non-linear power generation. The battery will charge whenever the renewable energy power is greater than to consumer load power as well as the battery will discharge whenever the renewable energy power is lesser than to consumer load power. The proposed model will be simulated using Matlab environment and analysis the proposed system results. Finally, simulation results are evaluated and validating the effectiveness of the proposed controller.